Application of Lemon Grass Compresses to Reduce Pain Scale in Older Age with Rhematoid Arthritis in the Perumnas Health Center Working Area Lubuklinggau City 2023 - Zuraidah, Zuraidah; Oktaviani, Eva; Fadillah, Anzelli; Wibowo, Wahyu Dwi Ari; Aprilyadi, Nadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the complementary treatments to reduce pain is lemongrass, which contains pharmacological and chemical effects and gives a spicy and warm effect, with bioactivity anti-bacterial and anti-inflammatory. The aim of the study is describing the results of the nursing implementation of warm lemon grass compresses for older adults with rheumatoid arthritis with chronic pain in the working area of the Perumnas Public Health Center, Lubuklinggau City, in 2023. This research used case study method with two subjects with rheumatoid arthritis. It found that warm lemongrass compresses for five straight days showed decreased pain intensity before and after the intervention. The decrease in the pain intensity of subjects I and II from the pain scale 6, with moderate pain category, decreased to pain scale 3, with mild pain intensity category. Warm lemongrass compresses can reduce pain intensity in older adults with rheumatoid arthritis.